Perlindungan Hukum Hak Waris Istri Kedua dari Perkawinan Tidak Tercatat Dikaitkan dengan Fungsi Pencatatan Perkawinan - Arif Bijaksana (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
The purpose of the study was to examine and analyze the legal protection of the wife's inheritance rights from unregistered marriages associated with the function of registering marriages with a comparative study of Islamic Fiqh and Law No. 1 of 1974. The research method of this writing is a normative juridical research that refers to the Qur'an. , Al-Hadith, Books of Fiqh, Legislation and related books that are relevant to this research. The data analysis technique used is a literature study which was analyzed qualitatively. The results of this study are that the second wife's inheritance rights from unregistered marriages are associated with the function of registering marriages. They have the right to inheritance which is owned jointly by the inheritance in the form of husband's innate property and joint property obtained by the second wife and her husband during the marriage period for the sake of a sense of justice and legal protection, legal protection of the second wife's inheritance rights in this study that to obtain inheritance rights and recognition to legalize marriages to religious courts. the results of the marriage itsbat as the legal basis for recording the marriage to the marriage registrar at the Office of Religious Affairs, then a Marriage Certificate Quotation Book is issued as authentic evidence that a marriage has been registered. So the legal protection and legal certainty of the second wife's inheritance rights from unregistered marriages associated with the function of recording marriages can obtain legal inheritance rights.